Deconstructing imperial representation - Schulz, Verena (Brill, 2019)
What literary strategies do Tacitus, Cassius Dio, and Suetonius apply in portraying Nero and Domitian? This book argues that the three authors respond to and deconstruct the positive accounts of imperial representation that were prevalent during the lifetimes of the two controversial emperors. They take up motifs from these earlier accounts, which they re-interpret to construct their own negative portraits.0Although Tacitus, Cassius Dio, and Suetonius discuss the same historical figures and events of early imperial Rome, they are rarely examined together in one volume. Verena Schulz offers the first combined reading of their works from a philological viewpoint, analysing the various rhetorical techniques and narratological devices that they display, and the different literary and historical discourses in which they are embedded
Habilitationsschrift, Faculty of Languages and Literatures at Ludwig-Maximilians-Universität München (LMU Munich), 2018
Keywords: Hochschulschrift; Domitian; Suetonius Tranquillus; Gaius; Cassius; Nero; Tacitus; Cornelius; Cassius Dio Cocceianus; Suetonius / approximately 69-approximately 122; Nero / Emperor of Rome / 37-68; Domitian / Emperor of Rome / 51-96; Rome / Historiography; Historiography; Rome (Empire); Dekonstruktion; Geschichtsschreibung; Selbstdarstellung